Protection Law To Child: (Based on Constitution Number 35 of 2014 concerning Change on Constitution Number 23 Year 2002 about Protection Children (“Law 35/2014”)) - Sri Utami; Hepy Krisman Laia; Muhammad Arif Sahlepi (International Journal of Law and Society, 2025)
The purpose of this study is to determine the forms of violence against children and how legal protection for children as victims of crime is according to Indonesian criminal law. Legal protection for children is an important issue that requires serious attention from various parties, including the government, society, and family. Children have basic rights that must be protected to ensure they grow and develop properly. This paper discusses the concept of legal protection for children, the legal basis underlying child protection in Indonesia, and the challenges and solutions that can be applied to improve legal protection for children.